Workplace Physical Activity Intervention Among Sedentary Workers: Initial Findings and Potential Implication (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Sedentary behaviour in the workplace has become a growing public health concern, particularly among office-based employees who spend prolonged hours seated at work. Given the amount of time adults spend at work, the workplace presents a valuable opportunity for implementing health promotion strategies aimed at increasing physical activity levels.This study aims to assess the effectiveness of a workplace physical activity intervention among sedentary workers in improving physical activity levels and aerobic endurance.Methods: This study used a pre- and post- test intervention design involving 11 participants from one enterprise. The target population consisted of office employees engaged in sedentary work for a minimum of 40 hours per week. At baseline, participants completed the IPAQ and assessments of the 6-Minute Walk Test and blood pressure measurements. Following baseline assessments, participants took part in a 21-day intervention programme tailored to their assigned group. Participants attended in-person exercise sessions three times per week. Each session lasted approximately 30 minutes and followed a structured format. The exercise programme primarily included: a 10-minute warm-up phase consisting mainly of aerobic exercises; a main part, which included approximately 10 functional mobility exercises, four strength exercises, five core stability exercises targeting deep trunk muscles; a 10-minute cool-down phase, focused primarily on stretching exercises suitable for the office environment. Upon completion of the active intervention phase, a three-month follow-up period was implemented, during which participants received ongoing support and supervision, but no additional structured interventions. Participation in the study was voluntary. Ethical approval for the study was obtained from the RSU Ethics Committee. This research was funded by the framework of the Plan of the European Union Recovery and Resilience Facility and the State Budget Grant RSU/LSPA-PA-2024/1-0013.Results: After-intervention results show that time spent sitting decreased by 13.5 hours, but the time employees reported spending walking during the previous week increased by 39 minutes. These findings suggest the formation of healthier lifestyle behaviours among participants.Conclusion: The findings provide insights into the potential benefits of integrating physical activity programmes into the workday. In addition, the study explores the feasibility and acceptability of implementing such interventions in real-world office settings.